Pengembangan Video Pembelajaran Materi Operasi Irisan dan Gabungan Dua Himpunan - Umardiyah, Fitri; Anggraini, Sindi Yulia (JoEMS (Journal of Education and Management Studies), 2022)
This study aims to develop instructional video media on the operation of slices and a combination of two sets of class VII SMP/MTS as a valid and practical student moral provision. This research is a research and development using the ADDIE Method (Analysis, Design, Development, Implementation, and Evaluation). The analysis technique of this study uses quantitative data in the form of scores from the validator, the value of the teacher's response, the value of student responses to video learning media in the form of questionnaire scores. Qualitative data in the form of interviews with education practitioners or mathematics teachers and criticism suggestions from validators. The results of this study resulted in a product in the form of a learning video. The feasibility of the product was obtained based on the results of the validation test and practicality test. Assessment by media experts got a score of 90% with a very valid classification or very feasible to use. Assessment by material experts got a score of 88% with a very valid or feasible classification. The results of the teacher's response questionnaire got a score of 90% with a very valid classification or very feasible to use. The results of the student response questionnaire got a score of 89.2% with a practical classification. Based on these results, it can be concluded that the video learning media assisted by Microsoft power point 2010 is feasible to use.